Isolated anti-ribosomal P antibodies are associated with reduced risk of renal and articular involvement in systemic lupus erythematosus patients. An observational study from one center - Mourad Elghali; Boussoukaya Yosr; Daadaa Syrine; Jguirim Mahbouba; Sakly Nabil; Hammami Sonia (Rheumatology)
Introduction The aim of the study was to compare the specific clinical manifestations of systemic lupus erythematosus (SLE) or laboratory findings between patients with and without anti-ribosomal P (anti-P) antibodies and to investigate possible associations between isolated anti-P antibodies and these features.